2015
DOI: 10.1097/ta.0000000000000620
|View full text |Cite
|
Sign up to set email alerts
|

An open, parallel, randomized, comparative, multicenter investigation evaluating the efficacy and tolerability of Mepilex Ag versus silver sulfadiazine in the treatment of deep partial-thickness burn injuries

Abstract: Therapeutic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 11 publications
1
37
0
Order By: Relevance
“…66 These characteristics were taken into consideration in the design of three RCTs ( The other two trials were multicentre studies that compared treatment of partial-thickness burn injuries with Mepilex Ag and silver sulphadiazine (SSD). In the RCT reported by Tang et al, 74 data from 153 patients were included in the analysis (Mepilex Ag, n=71; SSD, n=82). Although there was no significant difference in the healing rates of burns between the two groups, more burns healed in the Mepilex Ag group (n=13, 18%) compared with the SSD group (n=4, 5%; p=0.016).…”
Section: Burn Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…66 These characteristics were taken into consideration in the design of three RCTs ( The other two trials were multicentre studies that compared treatment of partial-thickness burn injuries with Mepilex Ag and silver sulphadiazine (SSD). In the RCT reported by Tang et al, 74 data from 153 patients were included in the analysis (Mepilex Ag, n=71; SSD, n=82). Although there was no significant difference in the healing rates of burns between the two groups, more burns healed in the Mepilex Ag group (n=13, 18%) compared with the SSD group (n=4, 5%; p=0.016).…”
Section: Burn Injuriesmentioning
confidence: 99%
“…74 Mepilex Ag and SSD were also compared in a multicentre trial by Silverstein et al 34 The American Burn Association/ children burn outcomes questionnaire, the short form (36) health survey and the EuroQol 5D health questionnaires were used to assess the consequences of burns, QoL and quality-adjusted life year (QALY) analysis. A total of 100 patients entered the study (Mepilex Ag, n=49; SSD, n=51).…”
Section: Silverstein Et Al (2011) 34mentioning
confidence: 99%
“…Silver‐impregnated foam dressing was reported in three RCTs, two of which were vs. SSD, and one vs. nanocrystalline silver . The patient population sizes ranged from 96 to 153, with one study (vs. nanocrystalline silver) in pediatric cases only .…”
Section: Resultsmentioning
confidence: 99%
“…Pain was reported by eight studies that compared the new antimicrobials with SSD/silver nitrate . Pain was assessed using either a 10‐point or 100‐point visual analog or face pain rating scale in small children in the included studies; however, reported results ranged from a week after treatment initiation to when the studies were completed at between three to six weeks.…”
Section: Resultsmentioning
confidence: 99%
“…46,[52][53][54] Silverbased dressings offer the antimicrobial benefits of topicals with less frequent dressing changes and better patient tolerability. [55][56][57] First introduced as a 10% ointment, mafenide is a topical sulfonamide with broad gram-positive and gram-negative activity, particularly Pseudomonas spp. 58 Mafenide offers the added benefit of eschar penetration for deep burns.…”
Section: Prophylactic Antimicrobial Selection Topicalsmentioning
confidence: 99%